Impacts on G.C.E Ordinary Level Results Among Bilingual Students and Tamil Medium Students ( A Comparative Based Research) - M.J. Fathima Sabrinas; M.J.F Sujani; MB Nowzath; MR. Rishad Muhammed (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
This research was carried out with the aim of identifying the impact of bilingual education by comparing the O/L results among the G.C.E O/L Tamil medium and bilingual students at KM/STR/AL-Marjan Muslim Ladies College, Sammanthurai. Writing, listening, and speaking skills are most important part in English which mainly committed by L2 learners. The examination department measures those students’ lower performance in their exam.  The Standard English has been going very low nowadays among L2 learners. But this problem is less in bilingual or L1 learners cause that the impact of bilingual and medium education and instruction. This is the reason researcher made the investigation about it. This research contacted among 2015 O/L batch students at KM/STR/Al-Marjan Muslim Ladies College Sammanthurai. The participants in this research were 26 students those were coming from bilingual and Tamil medium. The study technique of quantitative approach used. The data we're collected from using test strategies of pre-test,"20 minutes fun “and post-test than some questionnaire. The students have many problems to develop their knowledge of listening, speaking and even writing. After the investigation I found that the secondary learner (Tamil medium) of English student un interested to study the subject of English as their second language, they have the difficulties in those skills and have low level motivation in their learning process. Furthermore, it also proved by analyzing the O/L results of the same students. If they practice with writing, speaking and listening activity regularly, they can upgrade the knowledge and we can say that if those students studied in bilingual, they could improve those skills. This is mainly helping them to identify their lack of English skills. Engaging the writing activities also help them. I hope that the game "20 minutes fun" really make them to interesting to study the spelling of the word with fun. This different strategy gave new opportunity for them. Therefore, the objects were reached through the hard work of researcher, teacher and specially the students of 2015 O/L batch students. I hope that this research paper really helps the students to improve their English skills and knowledge and it will help to encourage the bilingual education in our area and it will make teachers and students to overcome the issues in their future.